Gender Differences in Acquisitive Delinquency: A Macro-Level Routine Activities Analysis - Roth, Jeffrey J. (American journal of criminal justice, 2016)
This study examines macro-level variation in juvenile theft and burglary arrest rates using a sample of 127 large cities in the United States. Independent variables were drawn from routine activities theory and included measures of guardianship (e.g., portion of families with both parents working, police to resident ratio, etc.), the number of motivated offenders (e.g., portion of the population under age 18), and the availability of suitable targets (e.g., poverty rates). Both ordinary least squares and weighted least squares regression analyses were performed. These analyses found that the significant predictors varied between burglary and theft. Additionally, there were differences in the predictors which significantly affected the arrest rates of male and female juveniles. However, within each offense the models explained similar portions of the overall variation in arrests for both genders.